2016
DOI: 10.1111/spc3.12229
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Toolkit of Emotion: What Do Sadness and Anger Do for Us?

Abstract: What do negative emotions do for people? We present a framework that defines the function of emotions as the degree to which discrete emotions result in better outcomes in particular types of situations. Focusing on sadness and anger, we review evidence related to the situations that elicit these emotions; the cognitive, physiological, and behavioral changes associated with the emotions; and the extent to which these changes result in demonstrably better outcomes in the type of situation that elicits the emoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 124 publications
2
55
0
Order By: Relevance
“…Similarly, Murube et al (1999) theorized that tears, beyond functioning as a request for help, also serve as a signal for offering help, for example in situations involving expressions of sympathy. Consistent with this, Provine, Krosnowski, and Brocato (2009) argued that emotional tears reliably signal sad feelings of the crier (see Cordaro, Keltner, Tshering, Wangchuk, & Flynn, 2016, for similar findings with regard to the acoustical attributes), and additional studies found that perceptions of sadness foster support behavior in others (Lench, Tibbett, & Bench, 2016). Interestingly, although mammals and certain bird species show distress vocalizations when being separated from a caregiver, humans seem to be unique when it comes to the production of emotional tears, which is maintained throughout the lifespan (Vingerhoets, 2013).…”
Section: The Function Of Human Emotional Tearsmentioning
confidence: 74%
“…Similarly, Murube et al (1999) theorized that tears, beyond functioning as a request for help, also serve as a signal for offering help, for example in situations involving expressions of sympathy. Consistent with this, Provine, Krosnowski, and Brocato (2009) argued that emotional tears reliably signal sad feelings of the crier (see Cordaro, Keltner, Tshering, Wangchuk, & Flynn, 2016, for similar findings with regard to the acoustical attributes), and additional studies found that perceptions of sadness foster support behavior in others (Lench, Tibbett, & Bench, 2016). Interestingly, although mammals and certain bird species show distress vocalizations when being separated from a caregiver, humans seem to be unique when it comes to the production of emotional tears, which is maintained throughout the lifespan (Vingerhoets, 2013).…”
Section: The Function Of Human Emotional Tearsmentioning
confidence: 74%
“…Emotion and counterfactual research would suggest that a state of regret would carry over to other domains (e.g. Lench, Bench, Darbor, & Moore, 2015;Lench, Tibbett, & Bench, 2016;Kwong, Wong, & Tang, 2013;Smallman, 2013), artificially inflating scores. Future research should specifically characterise the memories remembered by those explicitly identifying as procrastinators.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the anger literature [21] suggests that higher levels of anger expression (e.g., harmful behaviors of instigated incivility) increase one's stress and decrease one's well-being. Pertinent to our investigation is the argument [22,23] that anger expression (e.g., instigated incivility) causes the perpetrator to appear as a threat to others around, thus leading to emotional distress and poorer social functioning and interactions (e.g., cynicism) for the perpetrator. Indeed, Leiter and colleagues [24] provided initial evidence that incivility initiated by an employee was positively related to his/her own levels of emotional exhaustion and cynicism.…”
Section: Workplace Incivility and Job Burnoutmentioning
confidence: 93%